Therapeutic Effects of Naringin in Rheumatoid Arthritis: Network Pharmacology and Experimental Validation - Aihaiti, Yirixiati; Song Cai, Yong; Tuerhong, Xiadiye; Ni Yang, Yan; Ma, Yao; Shi Zheng, Hai; Xu, Ke; Xu, Peng (Frontiers in Pharmacology, 2021)
Abstract Rheumatoid arthritis is a chronic autoimmune disease characterized by persistent hyperplasia of synovial membrane and progressive erosion of articular cartilage. Disequilibrium between the proliferation and death of RA fibroblast-like synoviocytes (RAFLS) is the critical factor in progression of RA. Naringin has been reported to exert anti-inflammatory and antioxidant effect in acute and chronic animal models of RA. However, The therapeutic effect and underlying mechanisms of naringin in human RAFLS remain unclear. Based on network pharmacology, the corresponding targets of naringin were identified using Swiss TargetPrediction database, STITCH database and Comparative Toxicogenomics Database. Deferentially expressed genes (DEGs) in RA were obtained from GEO database. The protein-protein interaction (PPI) networks of intersected targets were constructed using STRING database and visualized using Cytoscape. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed, and the pathways directly related to pathogenesis of RA were integrated manually. Further, in-vitro studies were carried out based on network pharmacology. 99 targets genes were intersected between targets of naringin and DEGs. PPI network and topological analysis indicated that IL-6, MAPK8, MMP9, TNF, MAPK1 shared the highest centrality among all. GO analysis and KEGG analysis indicated that target genes were mostly enriched in (hsa05200)Pathways in cancer, (hsa05161) Hepatitis B, (hsa04380) Osteoclast differentiation, (hsa04151) PI3K-Akt signaling pathway, (hsa05142) Chagas disease (American trypanosomiasis). In-vitro studies revealed that naringin exposure was found to promote apoptosis of RAFLS, increased the activation of caspase3 and the ratio of Bax/Bcl-2 in a dose-dependent manner. Furthermore, treatment of naringin attenuated the production of inflammatory cytokines and matrix metalloproteinases (MMPs) in TNF-ɑ induced RAFLS. Moreover, treatment of naringin inhibited the phosphorylation of Akt and ERK in RAFLS. Network pharmacology provides a predicative strategy to investigate the therapeutic effects and mechanisms of herbs and compounds. Naringin inhibits inflammation and MMPs production and promotes apoptosis in RAFLS via PI3K/Akt and MAPK/ERK signaling pathway.